The Proton-activated Receptor GPR4 Modulates Intestinal Inflammation. (9th November 2017) - Wang, Yu; de Vallière, Cheryl; Imenez Silva, Pedro H; Leonardi, Irina; Gruber, Sven; Gerstgrasser, Alexandra; Melhem, Hassan; Weber, Achim; Leucht, Katharina; Wolfram, Lutz; Hausmann, Martin; Krieg, Carsten; et al.
Abstract: Background and Aims: During active inflammation, intraluminal intestinal pH is decreased in patients with inflammatory bowel disease [IBD]. Acidic pH may play a role in IBD pathophysiology. Recently, proton-sensing G-protein coupled receptors were identified, including GPR4, OGR1 [GPR68], and TDAG8 [GPR65]. We investigated whether GPR4 is involved in intestinal inflammation. Methods: The role of GPR4 was assessed in murine colitis models by chronic dextran sulphate sodium [DSS] administration and by cross-breeding into an IL-10 deficient background for development of spontaneous colitis. Colitis severity was assessed by body weight, colonoscopy, colon length, histological score, cytokine mRNA expression, and myeloperoxidase [MPO] activity. In the spontaneous Il-10 -/ - colitis model, the incidence of rectal prolapse and characteristics of lamina propria leukocytes [LPLs] were analysed. Results: Gpr4 -/ - mice showed reduced body weight loss and histology score after induction of chronic DSS colitis. In Gpr4 -/ - /Il-10 -/ - double knock-outs, the onset and progression of rectal prolapse were significantly delayed and mitigated compared with Gpr4 +/+ /Il-10 -/ - mice. Double knock-out mice showed lower histology scores, MPO activity, CD4 + T helper cell infiltration, IFN-γ, iNOS, MCP-1 [CCL2], CXCL1, and CXCL2 expression compared with controls. In colon, GPR4 mRNA was detected in endothelial cells, some smooth muscle cells, and some macrophages. Conclusions: Absence of GPR4 ameliorates colitis in IBD animal models, indicating an important regulatory role in mucosal inflammation, thus providing a new link between tissue pH and the immune system. Therapeutic inhibition of GPR4 may be beneficial for the treatment of IBD.